The wealth and poverty of nations : why some are so rich and some so poor - Landes, David S. (New York : W.W. Norton, 1998)
David S. Landes tells the long, fascinating story of wealth and power throughout the world: the creation of wealth, the paths of winners and losers, the rise and fall of nations. He studies history as a process, attempting to understand how the world's cultures lead to - or retard - economic and military success and material achievement.
Countries of the West, Landes asserts, prospered early through the interplay of a vital, open society focused on work and knowledge, which led to increased productivity, the creation of new technologies, and the pursuit of change. Europe's key advantage lay in invention and know-how, as applied in war, transportation, generation of power, and skill in metalwork. Even such now banal inventions as eyeglasses and the clock were, in their day, powerful levers that tipped the balance of world economic power. Today's new economic winners are following much the same roads to power, while the laggards have somehow failed to duplicate this crucial formula for success. The key to relieving much of the world's poverty lies in understanding the lessons history has to teach us - lessons uniquely imparted in this towering work of history.
Includes bibliographical references (p. [567]-635) and index.
Keywords: Wealth -- Europe -- History; Wealth -- History; Poverty -- Europe -- History; Poverty -- History; Regional economic disparities -- History; Economic history; Economic development -- Social aspects